PEMANFAATAN PROMOSI DIGITAL SEBAGAI STRATEGI PEMASARAN SERTA PENYUSUNAN LAPORAN KEUANGAN SEDERHANA PADA UMKM “DAPOER MALIKA” DI KELURAHAN KARANG JATI BALIKPAPAN - Sinaga, Ovigeria Subroto; Hanna Dhea CE Siregar; Kristina Natalia; Stevani Chalista; Rizky Novita Sari (Jurnal Pengabdian Indonesia (JPI), 2026)
Micro, Small, and Medium Enterprises (MSMEs) are one of the foundations of the Indonesian economy. Their development is inextricably linked to the evolving trends in sales models. Currently, the use of social media as a digital marketing method is crucial in assisting MSMEs in expanding their market and increasing sales turnover. STIE MADANI Balikpapan, through community service activities, is attempting to bridge the need for digital marketing methods and financial record-keeping for MSMEs around Balikpapan through Innovation Development (PI) activities with students. The MSME in this time is located in Karang Jati Village, Balikpapan, namely the Dapoer Malika MSME. Dapoer Malika produces several types of snacks. The PI activity helps this MSME market its products through social media and assists in preparing financial records. Keywords: MSME, Digital Marketing, Social Media, Bookkeeping